Smoking and its association with serum lipid levels - Pratap Singh Rajput, Devendra; Gulati, Divyani; Singh, Priti (International Journal of Medical Research and Review, 2016)
Objective: To compare the effect of smoking over lipid profile. Method: Total 100 subjects were included in this study, 50 were smoker and 50 non-smoker. All the factors other then smoking those can lead to dyslipidemia were ruled out. All patient’s fasting blood sample was collected and lipid profile was estimated. Data was analysed and‘t’ value was calculated. Results: Serum levels of total cholesterol (TC), triglycerides (TG), low density cholesterol (LDL), very low density cholesterol (VLDL) were found to be significantly high in smokers in comparison to non-smokers but high density cholesterol (HDL) did not any significant difference between two groups. Conclusion: Smoking affects lipid profile significantly, number and duration of smoking having correlation with serum lipoprotein levels but type of smoking (cigarette or biddi) doesn’t change the outcome.